2021
DOI: 10.3390/genes12121964
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses for Osteosarcoma in Leonberger Dogs Reveal the CDKN2A/B Gene Locus as a Major Risk Locus

Abstract: Dogs represent a unique spontaneous cancer model. Osteosarcoma (OSA) is the most common primary bone tumor in dogs (OMIA 001441-9615), and strongly resembles human forms of OSA. Several large- to giant-sized dog breeds, including the Leonberger, have a greatly increased risk of developing OSA. We performed genome-wide association analysis with high-density imputed SNP genotype data from 273 Leonberger cases with a median age of 8.1 [3.1–13.5] years and 365 controls older than eight years. This analysis reveale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Research studies over the past 10–15 years have sought to identify hereditary patterns of disease, and identify mono- or polygenic risk factors for specific sarcoma types. Multiple GWASs have been performed to identify genetic loci associated with the development of specific sarcoma types in dogs [ 44 , 45 , 46 , 47 , 48 , 49 ]. Major findings from these studies are summarized in Table 1 .…”
Section: Identification Of Predisposing Risk Factors For Sarcoma Deve...mentioning
confidence: 99%
“…Research studies over the past 10–15 years have sought to identify hereditary patterns of disease, and identify mono- or polygenic risk factors for specific sarcoma types. Multiple GWASs have been performed to identify genetic loci associated with the development of specific sarcoma types in dogs [ 44 , 45 , 46 , 47 , 48 , 49 ]. Major findings from these studies are summarized in Table 1 .…”
Section: Identification Of Predisposing Risk Factors For Sarcoma Deve...mentioning
confidence: 99%
“…The variant we identified occurs in approximately 10% of dogs in a germline resource of 722 dogs and other canids. In relation to previously described germline variants associated with canine osteosarcoma, it is 135 kb downstream (on the – strand) of the associated region described in greyhounds, 68 195 bp downstream of the variant identified in Rottweilers, 65 and 1.8 Mb upstream of the top associated SNP reported in Leonbergers 69 …”
Section: Discussionmentioning
confidence: 82%
“…In relation to previously described germline variants associated with canine osteosarcoma, it is 135 kb downstream (on thestrand) of the associated region described in greyhounds, 68 195 bp downstream of the variant identified in Rottweilers, 65 and 1.8 Mb upstream of the top associated SNP reported in Leonbergers. 69 The significant differences in age (and non-significant differences in OST) we observed between German Shepherds (which were younger and had shorter survival times), golden retrievers and Labrador retrievers (which were older and had longer survival times) also point to the potential influence of the genetic background. Because these three breeds have different average lifespans, it is difficult to ascertain whether German Shepherds (mean lifespan of 10.3 years) age more rapidly compared to Golden retrievers (mean lifespan 12 years) and Labrador retrievers (mean lifespan 12.6 years), [70][71][72] or if instead they age at the same rate, but their strong predisposition to HSA [70][71][72][73] and tendency towards shorter OST depress the breed's overall average survival.…”
Section: Breedmentioning
confidence: 80%
“…In previous studies, downregulation of p16 INK4A is also detected in canine OSA tissue and showed potential as a prognostic indicator [ 73 , 74 ]. Genome-wide studies identified 33 regions associated with canine osteosarcoma in several highly heritable breeds, including the greyhound, Rottweiler, Irish wolfhound [ 75 ] and Leonberger dog [ 76 ], and they include CDKN2A as one of the risk loci.…”
Section: Discussionmentioning
confidence: 99%